The effect of scad fish substitution and katuk leaf addition on the nutritional and sensory characteristics of nugget sticks - Sefanadia Putri; Nawasari Indah Putri Sejati; Tarissa Permata Hulul Aini (Arsip Keilmuan Gizi (AKG), 2026)
Vitamin A deficiency (VAD) is a serious health issue that can lead to night blindness, xerophthalmia, and a weakened immune system, which increases susceptibility to respiratory infections and diarrhoea in children. This study aimed to develop nugget sticks made from a combination of chicken meat and scad fish (50:50) with the addition of katuk leaves (Sauropus androgynus) as a protein-rich food product with potential provitamin A content. Protein plays a crucial role in the synthesis of Retinol Binding Protein (RBP), which is essential for transporting Vitamin A throughout the body. This experimental study tested three formulations of katuk leaf addition: F1 (5%), F2 (10%), and F3 (15%). Measured parameters included organoleptic tests (color, aroma, taste, texture), nutritional analysis using the Indonesian Food Composition Table (TKPI), consumer acceptance tests, and an evaluation of the product's economic value. The results indicated that F1 (5% katuk leaf addition) was the most preferred formulation overall. Per serving (35 g), these nuggets contain 94 kcal of energy, 6 g of protein, 5 g of fat, 7 g of carbohydrates, 41 mcg of retinol, and 296 mcg of beta-carotene. The acceptance test showed positive results, with an average food waste of less than 20% among panelists. Economically, the food cost for 50 units was Rp39,646, with a selling price of Rp1,982 per piece or Rp29,730 per 250 g package. In conclusion, these nugget sticks hold significant potential as a functional food entrepreneurship opportunity. Future research should involve laboratory-based nutritional analysis for more accurate validation.